Social Representations: A Review of Theory and Research from the Structural Approach - Wachelke, Joao; Università degli studi di Padova (2011)
The present paper is a review of the theoretical advances and empirical findings related to social representations according to the structural approach, a research stream that aims at studying the influence of social factors in thinking processes through the identification and characterization of relationship structures. The presentation of the approach begins with the baseline definitions of social representations according to a structural approach, moving on to an overview on the nature of representation elements, the relationships between representations and practices, cognitive scheme dimensions, central core theory, representation transformations and interaction context effects. In addition to positioning ourselves concerning polemic topics during the review, in the final section we evaluate briefly the current state and future perspectives of structural research on social representations, mostly addressing the problem of defining consensus, the difficulty of characterizing a collective construct from individual data, and the secondary importance of content in structural laws.